Fluoride Removal By Adsorption Using Oil Palm Waste - Puniran, Harun (Universiti Sains Malaysia, 2005)
Fluoride is commonly found in water and wastewater. Fluoride would not cause any bad impact to human and other life nature, up to certain amount only and for some higher amount or more than 1.0 mg/l, fluoride is no more as a requirement. From some studies, the permissible limits of fluoride for both humans and animals requirement was found to be very low. Therefore, the needs of studies to search for the best adsorbent, as an agent to remove high amount of fluoride is important. Most of the previous studies shown that adsorption is the best way to remove fluoride almost up to 95 % effectiveness and found that batch adsorption seems to be the favourite method to be used. This project is highlighted on oil palm waste such as fibre, sawdust, shell and ash as suitable and potential, yet economical materials for the purpose of fluoride removal. This project also used batch adsorption and all adsorbent were treated with acid. This study found that ash is the most effective adsorbent to remove fluoride at pH 2 and the experiment were carried out for about 240 minutes agitation time. Three main models suits with the isotherms generation are Freundlich model, BET model and Langmuir model. The present study found that Langmuir Isotherm followed the Fluoride adsorption effectively and the Langmuir was chosen due to the highest value of R2. The efficiency of removal achieved by ash as the adsorbent is about 92.5 %.